Transport discussion amidst climate challenges: Analysing student, media, and expert framings through the environmental protection process model - Vilja Varho; Nina A. Nygrén; Jari Lyytimäki (Elsevier, 2022)
The article examines media representations and views of experts and high school students on the future of transport with a particular focus on its implications for emissions of greenhouse gases. Focusing on Finland, it explores which key features and boundary conditions related to the climate policies of transport are framed as important or negligible. The analysis was based on the comprehensive environmental protection process model. Results show that the need for radical change was recognised both by students and experts but at the same time, rather cynical views regarding the possibilities to achieve these changes were presented by the media, experts, and students. Long-term impacts and visions were underrepresented in discussions, with the focus being mainly on short-term concerns and incremental changes.